Elucidating the Effect of Iron Speciation (Fe2+/Fe3+) on Crystallization Kinetics of Sodium Aluminosilicate Glasses. Issue 7 (15th April 2016) - Shaharyar, Yaqoot; Cheng, Justin Y.; Han, Edmund; Maron, Allyson; Weaver, Jamie; Marcial, José; McCloy, John S.; Goel, Ashutosh
Abstract : We report on the influence of Fe2 O3 on the crystallization kinetics of nepheline (Na2 O·Al2 O3 ·2SiO2 )‐based sodium aluminosilicate glasses. A series of glasses with varying Al2 O3 /Fe2 O3 content were synthesized in the system 25Na2 O–(25– x ) Al2 O3 – x Fe2 O3 –50SiO2 ( x varies between 0 and 5 mol%) through melt‐quench technique. A systematic set of experiments were performed to elucidate the influence of iron speciation (Fe 2+ /Fe 3+ ) on the crystallization kinetics of these glasses including: (1) obtaining the details of nonisothermal crystallization kinetics by differential scanning calorimetry, (2) determining the influence of heat treatment on the structure and iron coordination in glasses by X‐ray photoelectron spectroscopy and wet chemistry, and (3) following the crystalline phase evolution in glasses in air and inert environments by X‐ray diffraction and scanning electron microscopy. The crystallization of two polymorphs of NaAlSiO4 —carnegieite (orthorhombic) and nepheline (hexagonal)—was observed in all the glasses, wherein the incorporation of iron promotes the formation of nepheline over carnegieite while shifting the crystallization mechanism from surface to volume. The influence of environment (air versus inert) and iron content on the crystallization kinetics of these glasses is contextualized from the perspective of the devitrification problem usually observed in sodium‐ and alumina‐rich high level nuclear waste glasses.